The Effectiveness of Nurses’ Independent Interventions: Benson Relaxation and Five-Finger Hypnosis in Reducing Anxiety among Elderly Individuals in the Service Area of UPT. Puskesmas Lawawoi, Sidenreng Rappang Regency - Sulkifli Nurdin; Yuly Peristiowati; Prima Dewi Kusumawati (Universitas STRADA Indonesia, 2026)
Background: The growing elderly population has increased concerns regarding geriatric mental health, particularly anxiety disorders. Anxiety in older adults is often associated with declining physical function, chronic illness, social isolation, and reduced social support, which can negatively affect psychological well-being and quality of life (Beard et al., 2016; World Health Organization, 2022). If untreated, anxiety may worsen physical health conditions and reduce functional independence. Non-pharmacological nursing interventions are therefore needed due to their safety and accessibility. The novelty of this study lies in integrating Benson relaxation and five-finger hypnosis as nurse-led complementary interventions to reduce anxiety among community-dwelling elderly individuals. Purpose: This study aimed to analyze the effectiveness of Benson relaxation and five-finger hypnosis in reducing anxiety levels among elderly individuals in the service area of UPT Puskesmas Lawawoi, Sidenreng Rappang Regency, Indonesia. Methods: A quasi-experimental study with a pretest–posttest design was conducted among 54 elderly participants selected through simple random sampling. Participants were assigned to Benson relaxation (n = 27) and five-finger hypnosis (n = 27) groups. Anxiety levels were measured using a standardized instrument and analyzed using paired t-tests. Results: The findings showed a significant reduction in anxiety levels after the interventions (p < .001). This study provides evidence that combining relaxation response therapy with hypnosis-based techniques can effectively reduce anxiety among older adults. Conclusion: Benson relaxation and five-finger hypnosis are effective nurse-led complementary interventions that can be applied in community nursing programs to improve mental health among the elderly.